Pendidikan Aqidah Akhlak: Kunci Bahagia Dunia Akhirat Perspektif K.H. Husein Ilyas Mojokerto - Rahmat Lutfi Guefara; Robingun Suyud El Syam (Pusat Riset dan Inovasi Nasional, 2025)
Happiness is a word that is the obsession of every living human being, but many people are trapped in false happiness, so a discussion about happiness in this world and the hereafter is needed to be used as a guide. This article aims to explore the key to happiness in this world and the hereafter from the perspective of KH. Husain Ilyas Mojokerto, with a character study setting. The result: that the key to happiness in this world and the hereafter is to have three attitudes and behaviors, namely: As-Shofa, Al-Wafa, and Al-Jafa. As-Shofa means learning to cleanse the heart, learning from others who are more successful. Al-Wafa means keeping promises, not breaking your own words, not being a hypocrite. Al-Jafa means not being affected by praise, not being surprised when being cursed or insulted. These three concepts indicate that the essence of true happiness is not a matter of material things, but how to cultivate attitudes and behaviors that are reflections from the depths of the heart. This finding provides a direction for further research on true happiness that is multifunctional, namely the world and the hereafter. This study is expected to be useful for the direction of future research.